Pigmentos cerâmicos nanométricos a base de CeO2 dopado com Pr6O11, NiO e CoO - Casali, Graziela Pereira (2005)
In the last few years, the study of ceramic materials has increased very fast, mainly studies related to advanced ceramics. The several applications of these materials as ceramic pigments in nanometric scale justify more and more the need for a better understanding of the influence of the dopant addition on the final properties. In this present work, it was studied structural and morphological properties of ceramic pigments based on CeO2 doped with different molar percentages of praseodymium, nickel and cobalt. These properties were also analyzed under the influence of oxidizer (O2) and inert (N2) atmospheres applying different calcination temperatures. The goal of this work was to obtain nanosized ceramic pigments with. The chemical route adopted to obtain materials was the polymeric precursor method. It was obtained stable nanosized pigments, being observed the predominance of the dark red, brown and gray colors for systems doped with praseodymium, nickel and cobalt, respectively.